PROFIT MAXIMIZATION IN ISLAMIC BANKING: AN ASSEMBLAGE OF MAQASID SHARIAH CONCEPTION - Mukminin, Khairul (European Journal of Islamic Finance, 2019)
This paper aims to achieve enlightenment from Maqasid shariah in terms of profit maximization within Islamic banking. Therein the study conducting library-based approach for every single data obtained by virtues of books, articles, and other scholastic literatures and additionally different supporting approaches, namely Islamic jurisprudence, regulatory framework, accounting, and risk are engaged in this paper to exhibit more substantial apologia as regard of the topic. In respect of finding, making the best use of resources to achieve profit maximization within the bounds of the maqasid should be believed as maximization of other fundamental independent-rights, inter alia, right of Allah (zakah) and right of state (taxation). Moreover, the profit generated ought to bring refinement not solely to strengthen the standing of nifs mal (preservation of wealth), but also to nurture whosoever muslim person who successfully transforms its distress, time, and assets into financial gain. It is obvious that in shariah perspective specifically in the case of profit, nonetheless the right of Allah is the supreme, the right of human-being coming first after all worldly-obligations are adequately accomplished. Differently expressing, Maqasid al-shariah is a conception of precedence on how putting the best interest into the right time and the right place without inflicting suffering on the other interests with purpose that every single of interest could be on stage in the long run. For all practical purposes, this study call attention to the muslim public particularly by not losing sight of the fact apropos to the most fundamental of the maqasid principally in the circle of wealth namely, protection and establishment sequentially whereby IB should not be dictated to move with insistent haste by taking exhortations of greater distant of Maqasid provided by numerous contemporary Islamic scholars due to inherent nature of the bank per se. Through careful interpretation, this study encapsulates on how to derive and benefit from the maqasid by stages (protection, establishment, nurture) rather than in an instant manner.